2017
DOI: 10.1038/s41467-017-00646-w
|View full text |Cite
|
Sign up to set email alerts
|

Novel ecto-tagged integrins reveal their trafficking in live cells

Abstract: Integrins are abundant heterodimeric cell-surface adhesion receptors essential in multicellular organisms. Integrin function is dynamically modulated by endo-exocytic trafficking, however, major mysteries remain about where, when, and how this occurs in living cells. To address this, here we report the generation of functional recombinant β1 integrins with traceable tags inserted in an extracellular loop. We demonstrate that these ‘ecto-tagged’ integrins are cell-surface expressed, localize to adhesions, exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 58 publications
1
52
0
Order By: Relevance
“…Moreover, although the use of expression plasmids containing an epitope tag has proven useful for integrin studies (e.g. De Franceschi et al, 2016;Huet-Calderwood et al, 2017;Nader et al, 2016;Wang et al, 2015), there are potential artifacts with this approach including the level of expression of the tagged integrin and competition with endogenous integrin that are obviated by the use of Crispr/Cas9 genome editing. Although it has been shown that expression of cyto-tagged integrin β1 plasmid may influence its function (Galbraith et al, 2018), we did not detect any deficiency in the ability of the cyto-tagged β4 integrin to heterodimerize with α6 or of the reporter cells to adhere to laminin and activate Src.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, although the use of expression plasmids containing an epitope tag has proven useful for integrin studies (e.g. De Franceschi et al, 2016;Huet-Calderwood et al, 2017;Nader et al, 2016;Wang et al, 2015), there are potential artifacts with this approach including the level of expression of the tagged integrin and competition with endogenous integrin that are obviated by the use of Crispr/Cas9 genome editing. Although it has been shown that expression of cyto-tagged integrin β1 plasmid may influence its function (Galbraith et al, 2018), we did not detect any deficiency in the ability of the cyto-tagged β4 integrin to heterodimerize with α6 or of the reporter cells to adhere to laminin and activate Src.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, genome editing of integrins with Crispr/Cas9 technology has considerable potential. Although techniques describing integrin tagging have been previously described (De Franceschi et al, 2016;Huet-Calderwood et al, 2017;Nader et al, 2016;Wang et al, 2015), Crispr/Cas9 genomic engineering to knock-in fluorescent tags has not been used for this purpose. This approach is ripe for employment because it allows direct visualization of the integrin transcribed from the endogenous gene and it circumvents the use of ectopic expression systems that have the potential for artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…1G for a model). In addition to providing a tool for the long-term tracking of cell-surface expressed β integrins (Tsunoyama et al, 2018) or integrin internalization (Huet-Calderwood et al, 2017) of such β1 integrins, this technique also allows the study in great detail of the consequences of subtle sequence differences in the cytoplasmic tails of integrins. Thus, we used this strategy to study the functional role and dynamic differences of the alternatively spliced cytoplasmic tails of the ubiquitous β1A and muscle-specific β1D integrin, within the context of the FN-binding α5β1 integrin receptor.…”
Section: Extracellular Gfp Tagging Reveals Different Adhesion Patternmentioning
confidence: 99%
“…We next asked whether integrin-mediated protection from paclitaxel is also observed in vertebrate neurons. Since augmentation of a single integrin subunit can recruit endogenous subunit partners (Condic, 2001;Huet-Calderwood et al, 2017), we chose to transduce the human integrin β1 subunit 1 (ITGB1), a common subunit in all heteromeric dimers in adult DRG neurons in rodents (Plantman et al, 2008;Tomaselli et al, 1993;Wallquist et al, 2004). Lentivirus mediated delivery of ITGB1 was carried out in adult DRG neurons at 5DIV prior to treatment with either vehicle or 50nM paclitaxel for 72 hours starting at 12DIV, an experimental paradigm that had been previously shown to induce early and late signs of axon degeneration (Gornstein and Schwarz, 2017).…”
Section: Itgb1 Transduction In Adult Mouse Drg Neurons Prevents Axon mentioning
confidence: 99%
“…Ecto-tagged human β1 integrin (ecto-GFP-ITGB1) in lentiviral expression vector (Huet-Calderwood et al, 2017) was kindly provided by David Calderwood's lab at Yale University. pLENTI CMV Puro DEST (AddGene plamid #17452, gift from Eric Campeau) was purchased from AddGene.…”
Section: Lentiviral Packaging Of Human Ecto-tagged Itgb1mentioning
confidence: 99%